The Rock history reader - Cateforis, Theo (Routledge, 2013)
This volume is an eclectic compilation of readings that tells the history of rock as it has been received and explained as a social and musical practice throughout its six decade history. The readings range from the vivid autobiographical accounts of such rock icons as Ronnie Spector and David Lee Roth to the writings of noted rock critics like Lester Bangs and Chuck Klosterman. It also includes a variety of selections from media critics, musicologists, fanzine writers, legal experts, sociologists and prominent political figures. Many entries also deal specifically with distinctive styles such as Motown, punk, disco, grunge, rap and indie rock. Each entry includes headnotes, which place it in its historical context. This second edition includes new readings on the early years of rhythm & blues and rock 'n' roll, as well as entries on payola, mods, the rise of FM rock, progressive rock and the PMRC congressional hearings. In addition, there is a wealth of new material on the 2000s that explores such relatively recent developments as emo, mash ups, the explosion of internet culture and new media, and iconic figures like Radiohead and Lady Gaga. With numerous readings that delve into the often explosive issues surrounding censorship, copyright, race relations, feminism, youth subcultures, and the meaning of musical value, it continues to appeal to scholars and students from a variety of disciplines.